Amplification of Duffy binding protein-encoding gene allows Plasmodium vivax to evade host anti-DBP humoral immunity - Jean Popovici; Camille Roesch; Lenore L. Carias; Nimol Khim; Saorin Kim; Amelie Vantaux; Ivo Mueller; Chetan E. Chitnis; Christopher L. King; Benoit Witkowski (Nature Communications, 2020)
Duffy binding protein (DBP) of Plasmodium vivax is important for invasion and is a potential vaccine candidate. Here, the authors show that PvDBP gene amplification protects P vivax in vitro against invasion inhibitory human monoclonal antibodies and is associated to infection of patients with PvDBP binding inhibitory antibodies.